ISOLASI DAN KARAKTERISASI SENYAWA STEROID FRAKSI n-HEKSANA TERIPANG HITAM (Holothuria atra) ASAL PERAIRAN LEMUKUTAN KALIMANTAN BARAT - Abrori, Sayyidus Dzaki; Sapar, Ajuk; Gusrizal, Gusrizal; Harlia, Harlia; Prayitno, Dwi Imam (Tanjungpura University, 2025)
Black sea cucumber Holothuria atra is a marine organism from the family Holothuriidae, a source for developing raw pharmaceutical materials, and is abundant in the waters of Lemukutan Island. This study aims to identify steroid compounds from the n-hexane fraction of the black sea cucumber (H. atra) from Lemukutan waters using FTIR and ¹H-NMR instruments. The steps involved in this study include extraction (maceration and partition), phytochemical tests, fractionation (column chromatography), purification, and molecular structure identification. Phytochemical analysis of the n-hexane fraction of H. atra sea cucumber revealed the presence of secondary metabolites belonging to the groups of steroids, alkaloids, phenolics, terpenoids, and saponins. The result of the isolation was a relatively pure isolate with a weight of 0.0303 grams, yellowish white in color, and suspected to be a steroid compound. The results of the n-hexane fraction identification using FTIR showed the presence of several functional groups found in steroid compounds, such as aliphatic C-H bonds, olefinic =C-H bonds, C-O group, C=O group, C=C bond, and OH (hydroxyl) group. The results of the isolate identification using the ¹H-NMR instrument (500 MHz, CDClâ‚ƒ) showed chemical shift similarities to the Î²-sitosterol compound from two different references.